1983
DOI: 10.1007/bf01907213
|View full text |Cite
|
Sign up to set email alerts
|

Altered distribution of myosin isoenzymes in the cardiomyopathic Syrian hamster (BIO 8.262)

Abstract: Myosin of the ventricular myocardium of the cardiomyopathic Syrian hamster and of control animals was analysed using non-dissociating pyrophosphate electrophoresis. Three different myosin isoenzymes exhibiting different Ca2+ activated ATPase activities were demonstrated in the ventricular myocardium of the Syrian hamster. As shown by peptide mapping, ventricular myosin isoenzymes differ in their heavy chain composition. In the cardiomyopathic hamster a shift to myosins of lower Ca2+-activated ATPase activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…However, the amount of mRNA expressed at 2 days after birth is far less than at 20 days after birth, which in turn, is less than at 7 months. This pattern corresponds very closely to the ventricular myosin protein pattern seen during maturation of both rat and hamster heart (28,41); these data suggest that the mRNA represented by pVHC1 is coding for the a ventricular myosin heavy chain.…”
Section: ____________________________________________________________supporting
confidence: 74%
See 1 more Smart Citation
“…However, the amount of mRNA expressed at 2 days after birth is far less than at 20 days after birth, which in turn, is less than at 7 months. This pattern corresponds very closely to the ventricular myosin protein pattern seen during maturation of both rat and hamster heart (28,41); these data suggest that the mRNA represented by pVHC1 is coding for the a ventricular myosin heavy chain.…”
Section: ____________________________________________________________supporting
confidence: 74%
“…Some strains of this animal exhibit an autosomal recessive defect, a cardiomyopathy, which appears 30-45 days after birth (25)(26)(27). It has been reported that development of the cardiomyopathy is associated with an altered distribution of the three myosin isozymes (28,29); there is a shift from the V1 form of the ventricular myosin isozymes (which contains a higher ATPase activity than the V3 form) to the V3 form. It has been speculated that this shift in the myosin isozymes to the V3 form and to a lower ATPase activity is a compensatory process that may lead to a more economical working of the myocardial cell (29).…”
mentioning
confidence: 99%
“…The isomyocin pattern was not different in CMH and F1B before 220 days. Thus the shift from V1 to V3 seems to occur later than in other cardiomyopathic hamster strains (Wiegand et al , 1983; Malhotra et al , 1985; Lambert et al , 1995). Moreover, no difference in myosin isoform Ca 2+ ‐activted ATPase activity was observed between F1B and CMH at this stage.…”
Section: Discussionmentioning
confidence: 80%